European consensus-based recommendations for the diagnosis and treatment of Kawasaki disease – the SHARE initiative. (7th December 2018) - de Graeff, Nienke; Groot, Noortje; Ozen, Seza; Eleftheriou, Despina; Avcin, Tadej; Bader-Meunier, Brigitte; Dolezalova, Pavla; Feldman, Brian M; Kone-Paut, Isabelle; Lahdenne, Pekka; McCann, Liza; Pilkington, Clarissa; et al.
Abstract: Objectives: The European Single Hub and Access point for paediatric Rheumatology in Europe initiative aimed to optimize care for children with rheumatic diseases. Kawasaki disease (KD) is the most common cause of acquired heart disease in children and an important cause of long-term cardiac disease into adulthood. Prompt diagnosis and treatment of KD is difficult due to the heterogeneity of the disease but is crucial for improving outcome. To date, there are no European internationally agreed, evidence-based guidelines concerning the diagnosis and treatment of KD in children. Accordingly, treatment regimens differ widely. The aim of this study is to provide consensus-based, European-wide evidence-informed recommendations for diagnosis and treatment of children with KD. Methods: Recommendations were developed using the EULAR's standard operating procedures. An extensive systematic literature search was performed, and evidence-based recommendations were extrapolated from the included papers. These were evaluated by a panel of international experts via online surveys and subsequently discussed in three consensus meetings, using nominal group technique. Recommendations were accepted when ⩾80% agreed. Results: In total, 17 recommendations for diagnosis and 14 for treatment of KD in children were accepted. Diagnostic recommendations included laboratory and imaging workup for complete as well as incomplete KD. Treatment recommendations included the importance of early treatment in both complete and incomplete KD, use of intravenous immunoglobulin, aspirin, corticosteroids for high-risk cases, and other treatment options for those with resistant disease. Conclusion: The Single Hub and Access point for paediatric Rheumatology in Europe initiative provides international evidence-based recommendations for diagnosing and treating KD in children, facilitating improvement and uniformity of care.